The effect of whole body vibration on gait dynamics after chronic stroke in Pakistan; A Randomized Controlled Clinical Trial - Hafiz Syed Ijaz Ahmed Burq; Hossein Karimi; Ashfaq Ahmad; Syed Amir Gilani; Asif Hanif (Journal of the Pakistan Medical Association, 2021)
Objective: To determine the effect of whole body vibration (WBV) therapy on gait dynamics in chronic stroke patients in a tertiary care hospital. Methods: The present study was randomized, assessor-blinded, parallel-group, clinical trial conducted at Physiotherapy Department, Lahore General Hospital, Lahore, Pakistan, from November 2017 to April 2019. After taking written informed consent, 64 chronic stroke patients were randomly allocated (1:1) to routine physiotherapy (RP) group (n=32) and whole-body vibration (WBV) group (n=32) by computer random number generator method. Twelve sessions of vibration therapy were given to WBV group with an amplitude of 3 mm and frequency of 20Hz. Sessions comprises of 5 bouts of 120 seconds with 60 seconds rest intervals for 6 days/week x 2 weeks in erect standing position. The outcome measure was score of Timed Up and Go test (TUG test) and 10 Meter Walk test (10MWT) before and after intervention. Mann Whitney U Test and Wilcoxon Signed Rank test were used to analyze data. Results: After 2-week intervention, significant difference was seen in TUG, 10 Meter Walk test Slow Speed (10MWTSS), 10 Meter Walk test fast speed (10MWTFS) score for both treatment groups (p-value<0.05). However patients in WBV group had better improvement as compared to patients in the RP group. Conclusions: Initiation of walk and Walking Speed improved with Whole-body vibration therapy in chronic stroke survivors in Pakistan. Clinical Trial Number: IRCT20190328043131N1 Key Words: Stroke, Whole body Vibration, Rehabilitation, Walk Initiation, Walking Speed, Continuous...